Sustainable development in Asian manufacturing SMEs: Progress and directions - Jabbour, Ana Beatriz Lopes de Sousa; Ndubisi, Nelson Oly; Roman Pais Seles, Bruno Michel [UNESP] (Elsevier B.V., 2020)
This article identifies the factors that influence the environmental, social and financial performance of small and medium-sized enterprises (SMEs) in the manufacturing sector in Asia. Asian SMEs play an important role in both economic growth and the achievement of the region's sustainable development goals. For example, SMEs are key to employment creation and income distribution, and crucial to the growth of Asian exports. However, SMEs are also responsible for a large part of the world's consumption of resources, air and water pollution, and waste generation. Therefore, this article identifies and discusses the factors which contribute to Asian manufacturing SMEs' pursuit of sustainable development. An integrative literature review is conducted, and identifies that innovation and entrepreneurial orientation, governmental actions, and lean manufacturing systems are some of the prominent factors which drive Asian SMEs' financial, social and environmental performance. In addition, this article outlines future research avenues which could support Asian SMEs to move towards fully functioning sustainable development performance.
Keywords: Sustainability; Sustainable performance; Small and medium manufacturing enterprises; SMEs; Asia